2022
DOI: 10.1177/25152564221119347
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Interactions in Mitochondria-ER Contacts: A Possible Role in Parkinson's Disease

Abstract: Endoplasmic reticulum-mitochondria contact sites regulate various biological processes, such as mitochondrial dynamics, calcium homeostasis, autophagy and lipid metabolism. Notably, dysfunctions in these contact sites are closely related to neurodegenerative diseases, including Parkinson's disease, Alzheimer's disease and amyotrophic lateral sclerosis. However, details about the role of endoplasmic reticulum-mitochondria contact sites in neurodegenerative diseases remain unknown. In Parkinson's disease, intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…Alpha-synuclein aggregation is a pathological hallmark of PD. Emerging evidence has shown that alphasynuclein has profound functions at the mitochondria or to impact mitochondria, including mitochondrial oxidative phosphorylation, dynamics, mitophagy, Ca 2+ , and iron homeostasis 7,33,[55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-synuclein aggregation is a pathological hallmark of PD. Emerging evidence has shown that alphasynuclein has profound functions at the mitochondria or to impact mitochondria, including mitochondrial oxidative phosphorylation, dynamics, mitophagy, Ca 2+ , and iron homeostasis 7,33,[55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, α-syn was reported to bind and affect the function of ER-mitochondria contact sites. This binding might trigger mitochondrial and ER dysfunction as well as enhanced altered general and selective autophagy and thus impact the progression of the disease (Guardia-Laguarta et al, 2014;Paillusson et al, 2016;Gomez-Suaga et al, 2017;Liu et al, 2018;Erustes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type (WT) α-syn, a primarily cytoplasmic protein, was shown to associate with contact sites between the ER and mitochondria in cell lines and brain tissue obtained from mice and humans. Aggregation-prone clinical α-syn mutants displayed an altered interaction with these contacts, leading to a decrease in MCS function, increased mitochondrial fragmentation, and disturbed mitochondrial calcium signaling (Cali et al, 2012;Guardia-Laguarta et al, 2014;Paillusson et al, 2017;Erustes et al, 2022). These results suggest that the multiorganelle cytotoxic mechanism of α-syn might involve affecting organelle communication via MCSs.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The formation of α-syn fibrils increased in the presence of CL leading to the unfolded protein response (UPR) in the ER and mitochondria [87]. Interestingly, the localization of αsyn at ER-mitochondrial contact sites was also reported in different models [108,109]. These studies have shown that the overexpression of α-syn disrupted the physical contacts and Ca 2+ transfer between the two organelles, leading to alterations in mitochondrial metabolism.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 90%